2023
DOI: 10.1002/ps.7375
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative transcriptomic and proteomic analyses reveal the potential maintenance mechanism of female adult reproductive diapause in Chrysoperla nipponensis

Abstract: BACKGROUND: The green lacewing Chrysoperla nipponensis is an important natural enemy of many insect pests and exhibits reproductive diapause to overwinter. Our previous studies showed that adult C. nipponensis enters reproductive diapause under a short-day photoperiod. However, the molecular mechanism underlying diapause maintenance in C. nipponensis is still unknown.RESULTS: The total lipid and triglyceride content showed the reservation and degradation of energy during diapause in C. nipponensis. Thus, we pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…In the present study, total lipids, TAG, and FFAs accumulated during M and BD and were utilized during diapause. TAG is the main form of lipid storage and the most important energy substance in most diapause insects, and its content is closely related to the occurrence, maintenance, and termination of diapause [ 21 , 22 ]. Mamestra brassicae and Chrysoperla nipponensis reserve lipids before diapause [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, total lipids, TAG, and FFAs accumulated during M and BD and were utilized during diapause. TAG is the main form of lipid storage and the most important energy substance in most diapause insects, and its content is closely related to the occurrence, maintenance, and termination of diapause [ 21 , 22 ]. Mamestra brassicae and Chrysoperla nipponensis reserve lipids before diapause [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAG is the main form of lipid storage and the most important energy substance in most diapause insects, and its content is closely related to the occurrence, maintenance, and termination of diapause [ 21 , 22 ]. Mamestra brassicae and Chrysoperla nipponensis reserve lipids before diapause [ 22 , 23 ]. Lipid reserves remaining after termination of diapause are readily used for subsequent egg production [ 19 ], which was also observed in the mosquito Culex pipiens [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…During adult diapause, their body color changes from green to tan or yellowish, accompanied by the appearance of diapause spots. Based on our previous observations, we have found that starting on the fifth day after adult emergence, diapausing and non-diapausing female adults begin to exhibit differences in body color and weight [35]. Although C. nipponensis can sense short photoperiods and prepare for diapause upon adult eclosion, early laboratory studies revealed that experiencing short photoperiods during the larval stage also affects the physiological state of individuals [36].…”
Section: Introductionmentioning
confidence: 90%
“…Then, these C. punctiferalis larvae were dried in an oven (Yiheng, Shanghai, China) at 60 °C for 72 h. After drying, dry weight was measured by electronic microbalance (Sartorius analystic, Germany; N = 18). Water content was calculated as: (fresh weightdry weight)/fresh weight*100 (Chen et al 2023).…”
Section: Measurements Of the Weight And Nutrients Of C Punctiferalis ...mentioning
confidence: 99%
“…The triacylglycerol content of the sorghum and corn reared C. punctiferalis larvae were analyzed using a triglyceride assay kit (Cat No. A110-2-1; Nanjing Jiancheng Bioengineering Institute, Nanjing, Jiangsu, China) following the manufacturer's protocol (Chen et al 2023). Differences in weight and nutrients between the sorghum and corn-reared C. punctiferalis larvae were analyzed using Student's t-test at P < 0.05 (GraphPad Prism 8, GraphPad Software, Inc.; San Diego, CA, USA).…”
Section: Measurements Of the Weight And Nutrients Of C Punctiferalis ...mentioning
confidence: 99%